Postoperative Evaluation of Reduction Loss in Proximal Humeral Fractures: A Comparison of Plain Radiographs and Computed Tomography - Jia, Xiao‐yang (Orthop Surg, 2017)
OBJECTIVE: To compare postoperative CT images with plain radiographs for measuring prognostic factors of reduction loss of fractures of the proximal part of the humerus. METHODS: A total of 65 patients who sustained fractures of the proximal humerus treated with locking plates from June 2012 to October 2015 were retrospectively analyzed. There were 24 men and 41 women, with a mean age of 60.0 years (range, 22–76 years). According to the Neer classification system of proximal humeral fracture, there were 26 two‐part, 27 three‐part and 12 four‐part fractures of the proximal part of the humerus, and all fractures were treated with open reduction and internal fixation (ORIF) using locked plating. All postoperative CT images and plain radiographs of the patients were obtained. Prognostic factors of the reduction loss were the change of neck shaft angle (NSA) and the change of humeral head height (HHH). The change of NSA and HHH were evaluated by the difference between postoperative initial and final follow‐up measurement. Reduction loss was defined as the change ≥10° for NSA or ≥5 mm for HHH. The NSA and HHH were measured using plain radiographs and 3‐D CT images, both initially and at final follow‐up. The paired t‐test was used for comparison of NSA, change of NSA, HHH, and change of HHH between two image modalities. The differences between two image modalities in the assessment of reduction loss were examined using the χ(2)‐test (McNemar test). Intraclass correlation coefficients (ICC) were used to assess the intra‐observer and inter‐observer reliability. RESULTS: 3‐D CT images (ICC range, 0.834–0.967) were more reliable in all parameters when compared with plain radiographs (ICC range, 0.598–0.915). Significant differences were found between the two image modalities in all parameters (plain radiographs: initial NSA = 133.6° ± 3.8°, final NSA = 130.0° ± 1.9°, initial HHH = 17.9 ± 0.9 mm, final HHH = 15.8 ± 1.5 mm; 3‐D CT: initial NSA = 131.4° ± 3.4°, final NSA = 128.8° ± 1.7°, initial HHH = 16.8 ± 1.2 mm, final HHH = 14.5 ± 1.1 mm; all P < 0.05). In the assessment of reduction loss, the percentage was 16.9% (11/65) for the plain radiographs and 7.7% (5/65) for the 3‐D CT scans (P < 0.05). For the 5 patients with reduction loss, which were observed by two imaging modalities, the mean Constant–Murley score was 61.0 ± 1.6. The patients with reduction loss, observed only in plain radiographs but not CT images, had good shoulder function (Constant–Murley score: 82.7 ± 1.0). CONCLUSIONS: Our data reveal that 3‐D CT images are more reliable than plain radiographs in the assessment of the prognostic factors of reduction loss of fractures of the proximal part of the humerus with treatment of locking plates; this reliable CT technique can serve as an effective guideline for the subsequent clinical management of patients.